Endophytic Microorganisms for Improvement of Banana Vigour and Tolerance to Fusarium Wilt - Ting, Adeline Su Yien (2005)
This study explored the potential of endophytic microorganisms (EMS) isolated from wild bananas as biocontrol agents (BCAs) against Fusarium wilt caused by Fusarium oxysporum f. sp. cubense race 4 (FocR4) in susceptible banana ramets (Berangan cv. Intan). The fungal (Fusarium oxysporum (UPM31 PI)) and bacterial endophytes (Serratia marcescens (UPM39B3)) were established as effective BCAs; improving growth and vigour and enhancing tolerance of susceptible ramets to Fusarium wilt. They were antagonistic towards FocR4, with Percentage Inhibition of Radial Growth (PIRG) values of 65% and 63%, respectively. Inhibitory substances were produced in the form of volatile as well as non-volatile substances. The endophytes were also able to colonize the host tissues, including the roots and corms in artificial inoculation under laboratory conditions. The association of F. oxysporum (UPM31 PI) and S. marcescens (UPM39B3) with the host plants resulted in enhanced vegetative growth as shown by the increase in height, pseudostem diameter, root mass and total number of leaves ramet-'. Endophytes acted as elicitors in the production of inducible compounds associated with induced resistance (peroxidase, polyphenoloxidase, phenylalanine ammonia lyase, total soluble phenol and lignin content). The robust growth and occurrence of induced resistance subsequently enhanced tolerance of the ramets to Fusarium wilt based on parameters such as delay in onset of symptoms, lower percentages in disease incidence, disease severity, and epidemic rate. Inoculation with F. oxysporum singly was most effective followed by inoculation with mixture with S. marcescens (UPM31 Pl+UPM39B3). However, the survival and subsequent biocontrol efficacy of F. oxysporum (UPM31 PI) and S. marcescens (UPM39B3) might be vulnerable to the changing soil and environmental conditions. Populations of endophytes were not sustained over time. Therefore, further studies regarding formulation and application frequency and techniques, are essential to maximize the potential of F. oxysporum (UPM31P1) and S. marcescens (UPM39B3) as BCAs against Fusarium wilt of banana.